A REAL-TIME MONITORING IONIC LIQUID CHEMICAL SENSOR FOR HEAVY METALS AND TOXIC POLLUTANTS - YOGENDRAN, POONUDURAI (Universiti Teknologi PETRONAS, 2009)
Heavy metal and toxic pollutants in water samples cause severe health risks. Current methods used are time consuming; costly, and involve toxic organic solvents: Areal-time, ionic liquid monitoring chemical sensor is needed for instantaneous analysis of samples. Ionic liquids, ion compounds with low melting point, have become popular subject ofstudy because ofthenproperties especially non-toxicity, no vapor pressure and electrochemical properties. Recent studies suggest that ionic liquids can be used as solvents, reaction media or electrolyte, substituting volatile organic solvents, for heavy metals and toxic pollutant electrochemical activity. This research focuses on the use of ionic liquid for the development of a chemical sensor to detect and determine toxic analytes especially lead; Lead was chosen as the metal ion for this study due to its effects on children. [HMIM][TFSI] was chosen for this study due to its electrochemical and environmental properties and anodic stripping voltammetry (ASY* was chosen as analysis method due to its sensitivity range, convenience and cost effectiveness. Due to its simplicity and convenience, carbon paste method was chosen to incorporate the ionic liquid into the electrode design. Results show that the ionic liquid modified carbon paste electrodes measure higher current compared to the simple carbon paste electrodes. It is assumed that the modified electrodes are more sensitive to change in measured current compared to the simple ones. However, since [H3vHM][TFSI] is a hydrophobic ionic liquid, it alone is not capable of interacting with lead ion since metal ions are always hydrated in a solution. Metal ions were not depositing on the electrode surface and there were no peaks registered in the plot. Through research, it was known that ligands and other types of co-solvents can be used to aid metal ion penetration into the hydrophobic ionic liquid phase. Thus, it is hoped that the project can be expanded by incorporating these ligands into the electrode design in the near future. As a conclusion, the ionic liquid modified carbon paste electrodes shows promising signs to be used as chemical sensors for lead detections due their electrochemical and environmental aspects.